MORINGA OLEIFERA LEAF POWDER FOR TYPE 2 DIABETES: A PILOT CLINICAL TRIAL - Sissoko, Lassana; Diarra, Nouhoum; Nientao, Ibrahim; Stuart, Beth; Togola, Adiaratou; Diallo, Drissa; Willcox, Merlin Luke (African Journal of Traditional, Complementary and Alternative Medicines, 2023)
Background: Moringa oleifera Lam. (Moringaceae) leaves are commonly used for diabetes in Mali. This pilot clinical study aimed to evaluate its effect on post-prandial blood glucose in preparation for a larger trial. Methods: Diabetic patients and non-diabetic healthy volunteers (35 each) were asked to fast for 13 hours on three occasions. Blood glucose was measured before and after eating 100g of white bread (at 30, 60, 90, 120, 150 and 180 minutes). On their second and third study visits, they were given 1g and 2g respectively, of M. oleifera leaf powder, 30 minutes after eating the bread. The mean paired reduction in blood glucose at each time interval and the incremental area under the curve were calculated. Results: Ingestion of Moringa powder had no effect on blood glucose in non-diabetic participants, but in diabetic patients, it lowered blood glucose at 90 minutes. There was a trend towards lower incremental area under the curve when diabetic patients took 2g of Moringa. No side-effects were reported by any participant. Conclusions: Moringa oleifera leaf powder reduced post-prandial glycaemia in diabetic patients. A larger study is needed to define the optimal dose and to assess whether this translates into longer-term benefits.